2013
DOI: 10.3851/imp2531
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Pre-Therapy Viral Load on Virological Response to Modern First-Line Haart

Abstract: Background: We tested whether pre-HAART viraemia affects the achievement and maintenance of virological success in HIV-1-infected patients starting modern firstline therapies. Methods: A total of 1,430 patients starting their first HAART (genotype-tailored) in 2008 (median; IQR: 2006-2009) were grouped according to levels of pre-HAART viraemia (≤30,000, 30,001-100,000, 100,001-300,000, 300,001-500,000 and >500,000 copies/ml). The impact of pre-therapy viraemia on the time to virological success (viraemia ≤50 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
43
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 39 publications
(57 citation statements)
references
References 39 publications
(59 reference statements)
14
43
0
Order By: Relevance
“…Among the other confounders, very high pre-HAART viremia (>500,000 copies/mL) was significantly associated with poorer virological response, as previously observed [32] (Table S1). Of note, the lowest hazard of virological undetectability was found in patients with pre-HAART viremia >1,000,000 copies/mL.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…Among the other confounders, very high pre-HAART viremia (>500,000 copies/mL) was significantly associated with poorer virological response, as previously observed [32] (Table S1). Of note, the lowest hazard of virological undetectability was found in patients with pre-HAART viremia >1,000,000 copies/mL.…”
Section: Resultssupporting
confidence: 81%
“…Depending on methodologies available at the different clinical centers participating in this study, plasma viremia was determined using three different assays: the Roche Cobas CA/CTM version 2.0 (Mannheim, Germany), the Abbott RealTime HIV-1 (Chicago, Illinois), and the VERSANT HIV-1 Version 3.0 (Bayer Corporation, Diagnostics Division, Tarrytown, New York) [32], [33]. Previous studies demonstrated that even if there was not a uniform approach regarding the HIV-1 viral load detection, the results obtained by these assays correlated very well, only a few samples having a difference of more than 0.5 log 10 copies/mL [34], [35].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reasons for these inconsistencies remain unclear [12], but the limited time of follow-up in most studies should be noted. Also, it is well known that the viral load (VL) level at treatment initiation plays a determinative role in the first-line treatment response and the development of DRM [14]. …”
Section: Introductionmentioning
confidence: 99%
“…This was done by analyzing the time to second-line viral failure (VF) and the increase of CD4+ T-cells at 12 and 24 months of second-line ART. Moreover, since the baseline level of VL at initiation of first-line ART is an independent factor associated with decreased virological success [14], the effect of VL level at first-line ART failure on the second line outcome was investigated. For all analysis, patients were included over a period of 15 years, 1999–2014.…”
Section: Introductionmentioning
confidence: 99%